2020
DOI: 10.1038/s41467-020-18042-2
|View full text |Cite
|
Sign up to set email alerts
|

Advances and challenges in retinoid delivery systems in regenerative and therapeutic medicine

Abstract: Retinoids regulate a wide spectrum of cellular functions from the embryo throughout adulthood, including cell differentiation, metabolic regulation, and inflammation. These traits make retinoids very attractive molecules for medical purposes. In light of some of the physicochemical limitations of retinoids, the development of drug delivery systems offers several advantages for clinical translation of retinoid-based therapies, including improved solubilization, prolonged circulation, reduced toxicity, sustained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
75
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 87 publications
(76 citation statements)
references
References 133 publications
(294 reference statements)
1
75
0
Order By: Relevance
“…They play an active role in protein production, cellular metabolism and cell division [ 28 , 34 , 37 ]. Retinoids also affect the thickness and color of the skin, regulate the function of the sebaceous glands, and limit sebum production, as well as being responsible for hair and nail growth, and also influencing the distribution of melanin in the skin [ 27 , 30 , 35 ].…”
Section: Selected Substances Of Importance For Skin Functionmentioning
confidence: 99%
See 4 more Smart Citations
“…They play an active role in protein production, cellular metabolism and cell division [ 28 , 34 , 37 ]. Retinoids also affect the thickness and color of the skin, regulate the function of the sebaceous glands, and limit sebum production, as well as being responsible for hair and nail growth, and also influencing the distribution of melanin in the skin [ 27 , 30 , 35 ].…”
Section: Selected Substances Of Importance For Skin Functionmentioning
confidence: 99%
“…The anti-ageing effects of retinoids are mediated by three major types of skin cells: epidermal keratinocytes, dermal endothelial cells and fibroblasts [ 38 ]. Topically applied retinoids penetrate the keratinized epidermis and, to a lesser extent, the dermis and subcutaneous tissue [ 27 , 30 , 35 ]. A study in mice by Törmä et al showed that retinol esters accounted for 90% of the vitamin A in the epidermis, with retinol making up the remaining 10% [ 39 ].…”
Section: Selected Substances Of Importance For Skin Functionmentioning
confidence: 99%
See 3 more Smart Citations